The Effect of Softskill Training on Student Behavior Training at the Job Training Center - ahmad maftuh (RISTEC : Research in Information Systems and Technology, 2020)
This study aims to determine how much influence soft skills training has on student behavior during training using qualitative methods. The participants of this training were training students at the Balangan District Vocational Training Center for graphic design which consisted of two batches with a total of 32 people in 2019. Data were collected through direct observation by comparing the daily practice of students during the training with the material given in soft skills training. especially in applying the 5Rs (concise, neat, clean, caring and diligent). The results of the study show that soft skills training has not been able to significantly change student behavior in the habit of implementing 5R in the training environment. From the results of the study, the researchers suggested that the softskills training should be extended and evaluated and determined as one of the requirements to take part in the next technical training or in other words, training students cannot take the next technical training if the softskills training does not pass.